PREVALENCE AND PATTERN OF WORK-RELATED MUSCULOSKELETAL DISORDERS AMONG PRIMARY SCHOOL TEACHERS IN OVIA NORTH EAST, BENIN CITY, EDO STATE, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Work-related Musculo skeletal disorders are major health challenges for school teachers due to prolonged standing and repetitive tasks. Understanding the prevalence and patterns of musculoskeletal disorders among primary school teachers is essential for developing effective intervention strategies to improve their occupational health and well-being.Aim: The aim of this study was to determine the prevalence and pattern of work-related musculoskeletal disorders among primary school teachers in Ovia North-East, Benin City, Edo State, Nigeria.Methods: A cross-sectional descriptive study was conducted among Two hundred and sixty-seven (267) primary school teachers in Ovia North-East, Benin City, Edo State, Nigeria. Participants were selected using a consecutive sampling method. Data were collected with a structured self-administered questionnaire comprising sociodemographic/work related characteristics and an adapted Standardized Nordic Musculoskeletal Questionnaire. Descriptive statistics summarized participants’ characteristics and WMSD prevalence, while Chi-square tests assessed associations between variables at a 0.05 significance level.Results: Among 267 primary school teachers studied, the 12-month prevalence of musculoskeletal pain was highest in the lower back (28.5%), followed by the shoulder (21.7%) and upper back (18.7%). Pain affected work performance in 6.0% of respondents. Job characteristics such as longer teaching hours, poor posture and lack of ergonomic furniture were significantly associated with higher pain levels (p < 0.05).Conclusion: Musculoskeletal pain, particularly in the lower back, shoulder, and upper back, is highly prevalent among primary school teachers. The contributing factors include job-related characteristics such as longer teaching hours, poor posture and inadequate ergonomic support alongside sociodemographic factors like age and years of teaching experience. Improved workplace ergonomics, teacher training on posture, and adequate rest breaks are recommended to reduce the burden of musculoskeletal pain.
Keywords: Musculo-skeletal Pain; Shoulder pain; Lower back pain; Ergonomics; Teachers